A two-tiered methodology for the validation of promising plant growth promoting bacteria isolated from durum wheat rhizosphere - d’Amelio, Annalisa; De Santis, Michele Andrea; Giuzio, Luigia; Tozzi, Damiana; Campaniello, Daniela; Racioppo, Angela; Corbo, Maria Rosaria; Flagella, Zina; Bevilacqua, Antonio (Frontiers in Plant Science, 2025)
IntroductionPlant growth promoting bacteria (PGPB) are gaining increasing attention as a sustainable tool to support crop performance under environmental and agronomic stress conditions. However, the transition from laboratory to field is a challenge.MethodsSix PGPB strains from the rhizosphere of durum wheat were evaluated for their technological characteristics and agronomic performance, to identify suitable candidates for field conditions in a Mediterranean environment. The strains were studied for their resistance to two commercial fungicides, ability to persist in soil at different temperatures, and their growth over pH and temperature.Results and discussionThe strain 23P (Pseudomonas migulae) showed the best overall performance, with the highest resistance to fungicides and viability in soil; in addition, this microorganism enhanced shoot biomass and nitrogen uptake, increasing shoot-to-root ratio and N:P. The results support a selection strategy that includes both technological characterization and agronomic validation with a comprehensive and holistic approach from lab to field.